ZAKAT IBADAH SOSIAL UNTUK MENINGKATKAN KETAQWAAN DAN KESEJAHTERAAN SOSIAL - Syafiq, Ahmad (UIN Sunan Kudus, 2015)
Zakat is a religious service has two dimensions, namely uluhiyyah dimension(vertical) and insaniyyah dimensions / social ( horizontal ). Paying zakat isone of those who believe and fear Allah, and with the payment of zakat canimprove social welfare.